Reconstruction sequence and microsurgery in ectrodactyly-ectodermal dysplasia-cleft lip/palate syndrome: a case report - Gaviria-Pinzon, Jorge; Gutierrez Q., Jhon; Bermudez R., Luis; Nieto R., Luis (International Surgery Journal, 2022)
Ectrodactyly-ectodermal dysplasia-cleft lip/palate syndrome (EEC), is a rare entity characterized by alterations in the skin, hair, nails, apocrine glands and teeth, associated with dimorphisms in extremities and midface dysplasia. It is attributed to a mutation in the p63 gene. These patients require multiple surgical procedures to achieve functional goals. We present the surgical sequence of the interdisciplinary management performed on a patient diagnosed with this syndrome and the functional results obtained. A 5 months old female patient presented to our service with a suspected EEC syndrome. We present the case and the surgical procedures performed to achieve functional results. EEC syndrome is a low frequency patology which requires specialized surgical procedures of different kinds. Different surgical methods and techniques should be considered, due to the number and complexity of the malformations, which is why all human and technical resources must be available for its proper treatment.